STRATEGI PEMBELAJARAN BAHASA INDONESIA DALAM MENGEMBANGKAN KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS IV SD NEGERI MARABAHAN 2 - Laily Elsa Safitri; Johan Arifin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Writing narrative essays is one of the essential language skills that elementary school students need to master. However, many fourth-grade students still experience difficulties in developing ideas, organizing story sequences, and applying proper spelling and punctuation in their writing. This study aimed to describe the Indonesian language learning strategies implemented to develop narrative writing skills among fourth-grade students at SD Negeri Marabahan 2. The study employed a qualitative descriptive approach. Data were collected through observations, interviews, and documentation involving the fourth-grade classroom teacher and students. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation techniques. The findings revealed that the teacher implemented learning strategies through systematic lesson planning, the use of visual media in the form of picture series and short videos, Cooperative Learning, guided questions based on the 5W+1H concept, and continuous evaluation using writing assessment rubrics. These strategies contributed to improving students' narrative writing skills, particularly in generating ideas, organizing stories chronologically, and producing more complete narrative texts. The implementation of the learning strategies was supported by adequate school facilities, parental support, and students' characteristics, while limited learning time, students' concentration, vocabulary mastery, and writing mechanics remained the main challenges during the learning process.